Lymphoid tissue residency: A key to understand Tcf-1+PD-1+ T cells - Ma, Chaoyu; Zhang, Nu (Frontiers in Immunology, 2022)
During chronic antigen exposure, a subset of exhausted CD8+ T cells differentiate into stem cell-like or progenitor-like T cells expressing both transcription factor Tcf-1 (T cell factor-1) and co-inhibitory receptor PD-1. These Tcf-1+ stem-like or progenitor exhausted T cells represent the key target for immunotherapies. Deeper understanding of the biology of Tcf-1+PD-1+ CD8+ T cells will lead to rational design of future immunotherapies. Here, we summarize recent findings about the migratory and resident behavior of Tcf-1+ T cells. Specifically, we will focus on TGF-b-dependent lymphoid tissue residency program of Tcf-1+ T cells, which may represent a key to understanding the differentiation and maintenance of Tcf-1+ stem-like CD8+ T cells during persistent antigen stimulation.